Transformational Leadership Style in Higher Education: Scoping Literature Review - Da BOU; Rany SAM; Sinoeurn KHEUY (MASI Mandiri Edukasi, 2025)
Transformational leadership in higher education plays a crucial role in shaping institutional culture and driving positive change by inspiring faculty and students to achieve shared goals and embrace continuous improvement. The scoping review investigates the application and impact of transformational leadership in higher education institutions. By employing a systematic methodology, the study synthesizes literature published between 2019 and 2024, utilizing databases such as Google Scholar, ResearchGate, Europe PMC, ScienceDirect, CORE, and Scopus. The findings reveal that transformational leadership positively influences vital organizational outcomes, including job satisfaction, employee performance, and innovation within higher education institutions. However, challenges such as shared governance and academic autonomy hinder its implementation. This review highlights the fragmented literature and identifies essential themes, gaps, and future research directions, emphasizing the urgent need for a more comprehensive understanding of transformational leadership tailored to the unique dynamics of higher education. Future studies should explore adaptive strategies for implementing transformational leadership in diverse HEI contexts and investigate its long-term effects on institutional change and performance, highlighting the importance of continued research in this field.